Disseminated Histoplasmosis detected on peripheral blood smear examination in immunocompetent patients from non endemic region - Report of two cases from a tertiary care hospital - Neha Bagga; Kamna Sharma; Rajat K Tuteja; Satyaprakash Sharma; S R Negi; S L Mathur (Wolters Kluwer Medknow Publications, 2020)
Histoplasmosis is an opportunistic systemic infection caused by inhaling spores of a thermal dimorphic fungus Histoplasma capsulatum. Disseminated histoplasmosis is the most common form associated with acquired immune deficiency syndrome (AIDS). However, only a few cases of disseminated histoplasmosis are reported in immuno-competent hosts. Most infections in the immunocompetent hosts are asymptomatic or result in mild pulmonary disease. However the presence of Disseminated Histoplasmosis in immunocompetent host probably results due to prolonged exposure and delayed presentation We report two cases of progressive disseminated histoplasmosis in two immunocompetent patients from non-endemic region in Western Rajasthan, India. Also in both the cases, the first diagnosis was suggested by a peripheral blood smear, which is not a classical biological diagnostic method for fungal infection. Careful examination of Peripheral blood smear along with correct clinical history can aid in early diagnosis of disseminated histoplasmosis even in immunocompetent patients.